2013
DOI: 10.5603/ait.2013.0017
|View full text |Cite
|
Sign up to set email alerts
|

Residual neuromuscular block in elderly patients after surgical procedures under general anaesthesia with rocuronium

Abstract: Residual paralysis remains a major problem in geriatric clinical anaesthesia. Neuromuscular function monitoring is obligatory, and pharmacological reversal of relaxation should be advised in geriatric patients after using relaxants for general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 32 publications
5
28
1
2
Order By: Relevance
“…In a study examining neuromuscular block induced with vecuronium, Baillard et al [42] reported a higher median age in a group of patients with a detected PORC defined as TOFR < 0.7 compared to patients with greater TOFR values. This was confirmed by the results of two large prospective studies with residual blockade as the primary end-point in elderly patients after the administration of rocuronium [5,43]. In a group of 415 patients Pietraszewski et al [5] proved that if rocuronium is administered empirically and the blockade is not reversed by the end of anaesthesia, PORC (TOFR < 0.9) is commonplace, occurring in 89% of patients aged 65 and older with as many as 44% with TOFR < 0.7.…”
Section: Residual Neuromuscular Block As a Significant Clinical Problsupporting
confidence: 67%
See 3 more Smart Citations
“…In a study examining neuromuscular block induced with vecuronium, Baillard et al [42] reported a higher median age in a group of patients with a detected PORC defined as TOFR < 0.7 compared to patients with greater TOFR values. This was confirmed by the results of two large prospective studies with residual blockade as the primary end-point in elderly patients after the administration of rocuronium [5,43]. In a group of 415 patients Pietraszewski et al [5] proved that if rocuronium is administered empirically and the blockade is not reversed by the end of anaesthesia, PORC (TOFR < 0.9) is commonplace, occurring in 89% of patients aged 65 and older with as many as 44% with TOFR < 0.7.…”
Section: Residual Neuromuscular Block As a Significant Clinical Problsupporting
confidence: 67%
“…This was confirmed by the results of two large prospective studies with residual blockade as the primary end-point in elderly patients after the administration of rocuronium [5,43]. In a group of 415 patients Pietraszewski et al [5] proved that if rocuronium is administered empirically and the blockade is not reversed by the end of anaesthesia, PORC (TOFR < 0.9) is commonplace, occurring in 89% of patients aged 65 and older with as many as 44% with TOFR < 0.7. In younger patients, TOFR values of < 0.9 and < 0.7 were observed in 77 and 20% of patients, respectively.…”
Section: Residual Neuromuscular Block As a Significant Clinical Problsupporting
confidence: 67%
See 2 more Smart Citations
“…Various reports have identified different factors to have association with the occurrence of postoperative residual neuromuscular blockage including age and gender of the patient, type and dose of muscle relaxant used, type and dose of reversal drug used, type of anaesthesia used intraoperatively, duration of surgery and anaesthesia, time of last dose given and reversed, presence of metabolic derangement, hypothermia, opioid and antibiotics given in the recovery [4,[17][18][19][20][21]. However, the reported magnitudes and associated factors may be different from developed to developing countries and have shown different time trends as the interplay between the various socioeconomics, clinical practice, and limited resources alter in sub-Saharan country setting.…”
Section: Introductionmentioning
confidence: 99%